2018
DOI: 10.1590/rbz4720160328
|View full text |Cite
|
Sign up to set email alerts
|

Organic selenium supplementation is cost-effective for increasing the number of seminal doses produced by sexually mature boars

Abstract: The present experiment was carried out to evaluate the economic viability of supplementing boar diets with organic selenium aiming to increase the number of seminal doses of sexually mature boars. Twelve boars were divided into three groups: control group received 0.3 mg kg −1 Se from sodium selenite (n = 4), inorganic group received 0.5 mg kg −1 Se from sodium selenite (n = 4), and organic group received 0.5 mg kg −1 Se from Sel-Plex TM (Alltech, Inc., n = 4). The experiment was conducted within 10 weeks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Besides, recently in an interesting cost–benefit analysis [109], it has been shown that boars fed organic Se-based (0.5 mg per kg) diet produced around 23% higher doses of semen per week compared to those maintained on inorganic Se diets (0.5 mg per kg). A significant increase in revenue (26%) was also observed in this study [109]. In any case, additional animal studies reporting the effects of Se supplementation on the male reproductive efficiency in different animal models are presented in Table 4.…”
Section: Role Of Selenium In Male Reproductionmentioning
confidence: 99%
“…Besides, recently in an interesting cost–benefit analysis [109], it has been shown that boars fed organic Se-based (0.5 mg per kg) diet produced around 23% higher doses of semen per week compared to those maintained on inorganic Se diets (0.5 mg per kg). A significant increase in revenue (26%) was also observed in this study [109]. In any case, additional animal studies reporting the effects of Se supplementation on the male reproductive efficiency in different animal models are presented in Table 4.…”
Section: Role Of Selenium In Male Reproductionmentioning
confidence: 99%
“…After 45 days of Se supplementation, the semen ejaculate volume, sperm motility and viability were significantly higher in Se supplemented diet compared to the control group; organic Se had a much faster effect compared to inorganic Se [ 144 ]. In addition, a recent study reported that boars fed on organic Se-based diet (0.5 mg per kg) determined a 23% increase in the sperm concentration per week compared to inorganic Se-based diet (0.5 mg per kg) [ 145 ]. Thus, clearly there is marked improvement in the structural and functional factors that define male fertility and sperm functions (refer to Figure 3 ), but questions on the precise dose, optimal form of Se, and duration of safe supplementation remain unanswered and warrants further research.…”
Section: Selenium and Male Reproductionmentioning
confidence: 99%
“…It was observed an increase of 23% in semen AI-doses production, resulting in a 37% reduction in the cost of diet per dose produced by boars fed SeMet compared to that fed sodium selenite. The authors pointed out that the total revenue produced by the organic group was 26% higher than the inorganic one (MARTINS et al, 2014(MARTINS et al, , 2018.…”
Section: Organic Selenium In Boar Reproductionmentioning
confidence: 99%
“…From the results obtained in two semen evaluations, an average per characteristic was calculated. An indicator (score) represented these values' sum and allowed the animal ranking (I) according to Martins et al (2018).…”
Section: Distribution Of Animals Into Experimental Groupsmentioning
confidence: 99%
See 1 more Smart Citation